2013
DOI: 10.1152/ajpcell.00026.2013
|View full text |Cite
|
Sign up to set email alerts
|

RACK1 interacts with filamin-A to regulate plasma membrane levels of the cystic fibrosis transmembrane conductance regulator

Abstract: Smith L, Litman P, Kohli E, Amick J, Page RC, Misra S, Liedtke CM. RACK1 interacts with filamin-A to regulate plasma membrane levels of the cystic fibrosis transmembrane conductance regulator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…In addition, liver fibrosis can induce a hypoxic environment, which promotes the production of angiogenic factors, including VEGF and angiopoietin, and these factors lead to increased angiogenesis 4345. Excessive levels of ECM deposition and angiogenic factors lead to LSEC capillarization, which results in increased vascular resistance and portal hypertension 46. The data demonstrated that the levels of angiogenic factors, including VEGF and angiopoietin-2, were significantly increased in the serum of CCl 4 -treated mice.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, liver fibrosis can induce a hypoxic environment, which promotes the production of angiogenic factors, including VEGF and angiopoietin, and these factors lead to increased angiogenesis 4345. Excessive levels of ECM deposition and angiogenic factors lead to LSEC capillarization, which results in increased vascular resistance and portal hypertension 46. The data demonstrated that the levels of angiogenic factors, including VEGF and angiopoietin-2, were significantly increased in the serum of CCl 4 -treated mice.…”
Section: Discussionmentioning
confidence: 94%
“…A major interaction candidate revealed by the MS analysis was RACK1 (Table 1 ), which is known to play important roles in protein targeting and membrane retention 31 , 33 37 . Therefore, we hypothesized that RACK1 contributes to NBCn1 membrane targeting and/or retention.…”
Section: Resultsmentioning
confidence: 99%
“…This method was also used in the study identifying the specific site phosphorylated by PKCδ, which phosphorylates Nrf2 at serine 40 3 . Since peptides competitively bind to a protein, the principle may also be applied to an in vitro GST pull-down assay to identify a binding motif 10,11 . Moreover, this peptidomimetic method may also be applicable to the identification of other post-translational modifications, such as acetylation at lysine residues.…”
Section: Discussionmentioning
confidence: 99%